Reversibility of lipoatrophy in HIV-infected patients 2 years after switching from a thymidine analogue to abacavir: the MITOX Extension Study - Martin, Allison; Smith, Don E; Carr, Andrew; Ringland, Clare; Amin, Janaki; Emery, Sean; Hoy, Jennifer; Workman, Cassy; Doong, Nicholas; Freund, Judith; Cooper, David A (AIDS (London), 2004)
To determine if long-term improvement in HIV lipoatrophy can be attained by substitution of thymidine analogues zidovudine (ZDV) or stavudine (d4T) with abacavir (ABC). Long-term follow-up (104 weeks) of a randomized, open-label study. Seventeen ambulatory HIV clinics in Australia and London. Patients with HIV lipodystrophy were randomized to switch from a thymidine analogue to ABC, while continuing all other antiretroviral therapy (ABC arm) (n = 42) or continue current therapy (ZDV/d4T arm) (n = 43). At week 24, all control patients could switch to ABC. Of the original 111 patients randomized, 85 had long-term follow-up data, with 77 having imaging data available at 104 weeks. The primary endpoint was time-weighted change in limb fat mass, measured by dual-energy X-ray absorptiometry (DEXA). At week 104, the mean increase in limb fat for the ABC and ZDV/d4T group was 1.26 +/- 2.02 kg and 0.49 +/- 1.38 kg, respectively. The time-weighted change for limb fat was significantly different between the two arms (0.43 kg; P = 0.008). On-treatment analysis demonstrated a trend for increased limb fat in patients in the ABC arm. Visceral fat accumulation, buffalo hump, self-assessed lipodystrophy or the lipodystrophy case definition score (LCDS) did not improve. In patients with moderate-to-severe lipodystrophy, significant improvements in subcutaneous fat continued over 104 weeks after switching from a thymidine analogue to ABC. Nevertheless, the lipodystrophy syndrome was still evident, indicating additional strategies need evaluating.